DEVELOPMENT OF F1 HYBRID OF CUCUMBER SPECIFIED FOR GREENHOUSES - H. A. Adday; A. H. Fathi (مجلة الأنبار للعلوم الزراعية, 2024)
The study was carried out in the fall 2021 and spring 2022 seasons in one of the greenhouses belonging to the College of Agriculture / University of Anbar to study and evaluate the performance of fifteen single crosses by half-crossing and six inbreds and a comparison cross (KANZ). The experiment was carried out according to the randomized complete block design (RCBD) with three replications, each replication containing 22 experimental units. The results showed the superiority of the hybrid 5×6 in stem diameter, number of flowers per nod, total number of flowers, plant yield, fruit length, and fruit diameter, reaching 12.66 mm, 2.06 flower nod-1, 81.71 flower plant-1, 3.99 kg. Plant-1, 18.50 cm, 3.9 cm, respectively. The hybrid 2×5 excelled in the characteristic of the ratio of fruit set, reaching 55.47%, compared to the comparison hybrid (Kanz). The hybrids gave different performances in the rate of hybrid vigor, which reached the highest in yield, which amounted to 55.66% for the 4×6 hybrid, ratio of fruit set, which amounted to 29.22% for the 4×5 hybrid, and in the number of total flowers, which amounted to 25.42% for the 2×3 hybrid. The average number of flowers per not, which amounted to 19.4% for the hybrid 2×3. In stem diameter, it reached 15.26% for the 3×6 hybrid, and in fruit diameter and fruit length, they reached 3.34% and 3.23% for the 5×6 hybrid, respectively.